On space and time - Connes, Alain (Cambridge University Press, 2008)
What is the true nature of space and time? These concepts are at the heart of science, but they remain deeply wrapped in enigma. Their structure at both the smallest pre-subatomic and the largest cosmological levels continues to defy modern physics and may require revolutionary new ideas for which science is still grasping. This unique volume brings together world leaders in cosmology, particle physics, quantum gravity, mathematics, philosophy and theology, to provide fresh insights into the deep structure of space and time. Andrew Taylor explains the evidence for dark matter and dark energy. Shahn Majid argues that space and time should be quantum. Roger Penrose explains what in his view comes before the 'Big Bang'. Alain Connes argues that matter is geometry as a fine structure to spacetime. Michael Heller explores the philosophical and theological implications of spacetime. John Polkinghorne argues for a theory of how time unfolds